Fast Delayed Emission in New Pyridazine-Based Compounds - Krotkus, Simonas; Matulaitis, Tomas; Diesing, Stefan; Copley, Graeme; Archer, Emily; Keum, Changmin; Cordes, David B.; Slawin, Alexandra M. Z.; Gather, Malte C.; Zysman-Colman, Eli; Samuel, Ifor D. W. (Frontiers in Chemistry, 2021)
Three novel donor-acceptor molecules comprising the underexplored pyridazine (Pydz) acceptor moiety have been synthesized and their structural, electrochemical and photophysical properties thoroughly characterized. Combining Pydz with two phenoxazine donor units linked via a phenyl bridge in a meta configuration (dPXZMePydz) leads to high reverse intersystem crossing rate krISC = 3.9 ∙ 106 s-1 and fast thermally activated delayed fluorescence (TADF) with <500 ns delayed emission lifetime. Efficient triplet harvesting via the TADF mechanism is demonstrated in OLEDs using dPXZMePydz as the emitter but does not occur for compounds bearing weaker donor units.